Eccentric exercise in aging and diseased skeletal muscle: good or bad? - Lovering, Richard M. (American Physiological Society, 2013)
Evidence is accumulating regarding the benefits of exercise in people who are more susceptible to injury, such as the elderly, or those with a neuromuscular disease, for example Duchenne muscular dystrophy (DMD). There appears to be a consensus that exercise can be safely performed in aging and diseased muscles, but the role of eccentric exercise is not as clear. Eccentric (lengthening) contractions have risks and benefits. Eccentric contractions are commonly performed on a daily basis, and high-force voluntary eccentric contractions are often employed in strength training paradigms with excellent results; however, high-force eccentric contractions are also linked to muscle damage. This minireview examines the benefits and safety issues of using eccentric exercise in at-risk populations. A common recommendation for all individuals is difficult to achieve, and guidelines are still being established. Some form of exercise is generally recommended with aging and even with diseased muscles, but the prescription (frequency, intensity, and duration) and type (resistance vs. aerobic) of exercise requires personal attention, as there is great diversity in the functional level and comorbidities in the elderly and those with neuromuscular disease.